Social media driven mediatization of youth in BRICS - Zamaswazi P. Cele; Marina G. Shilina; Ndivhuho Tshikovhi (RUDN Journal of Studies in Literature and Journalism)
Over the years, social media has emerged as the largest source for global communication. In post-COVID-19 times and especially in the New Reality, social media consumption patterns have shifted significantly. As these platforms become more open and widespread, they also exacerbate issues related to information and news consumption, mediation and mediatization. This is particularly crucial for young populations in developing nations such as those in the BRICS (Brazil, Russia, India, China, and South Africa) group, who face both high external pressures and internal challenges. Examines the state of social media usage among youth in BRICS countries, focusing on data from 2023 to find the specificity of social media driven mediatization. Research indicates that youth in BRICS nations have been active social media users over the past decade. The authors identify key consumption patterns among Generation Z and millennials in Brazil, Russia, India, China, and South Africa in 2023, and conduct a comparative analysis of social media usage in these nations. Provides a brief overview of the mediatized challenges posed by social media in the BRICS nations, particularly the spread of fake news. The study reveals that the increasing reliance on social media for news and information by younger generations underscores the need for identifying specific field of media studies in BRICS countries (Media Studies based on the concept of BRICSology). The conclusion highlights the social media consumption patterns and challenges that need attention in future research.